Advances in Experimental Medicine and Biology
DOI: 10.1007/0-387-30172-0_17
|View full text |Cite
|
Sign up to set email alerts
|

N-Acetylaspartate as a Marker of Neuronal Injury in Neurodegenerative Disease

Abstract: Considerable evidence suggests that normal aging is associated with gradual impairment of memory functioning [1]. The medial temporal lobe, especially the hippocampus, plays a central role in declarative memory processing [2]. However, magnetic resonance imaging (MRI) studies have produced controversial results concerning the age-related hippocampal volume loss, which could be due in part to the non-specificity of volume shrinkage as an indicator for neuron loss. In contrast to volume, NAA is generally conside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
2
2

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(59 citation statements)
references
References 50 publications
2
53
2
2
Order By: Relevance
“…As stated above, myo- inositol is involved in cell volume regulation, and thus, may be directly influenced by edema and/or osmotic changes [36, 43-47, 54-56]. Further, as described below, normalization to NAA may be susceptible to bias due to neurodegeneration [60], which may or may not be attributed to chronic neuroinflammation [35]. Conversely, normalization to creatine, often considered a stable metabolite, may be less susceptible to bias than NAA.…”
Section: Using Imaging To Measure Neuroimmune Biomarkersmentioning
confidence: 99%
See 1 more Smart Citation
“…As stated above, myo- inositol is involved in cell volume regulation, and thus, may be directly influenced by edema and/or osmotic changes [36, 43-47, 54-56]. Further, as described below, normalization to NAA may be susceptible to bias due to neurodegeneration [60], which may or may not be attributed to chronic neuroinflammation [35]. Conversely, normalization to creatine, often considered a stable metabolite, may be less susceptible to bias than NAA.…”
Section: Using Imaging To Measure Neuroimmune Biomarkersmentioning
confidence: 99%
“…Similarly, brain choline levels are influenced by dietary choline consumption [72] and psychiatric comorbidities [73, 74]. NAA is a putative neuronal marker [35], and abnormally low levels may reflect neuronal degeneration [60], but it is not necessarily specific to neuroimmune signaling. In addition to MRS, several other imaging markers exist.…”
Section: Using Imaging To Measure Neuroimmune Biomarkersmentioning
confidence: 99%
“…135 Reductions of hippocampal NAA, a marker for viable neurons, have been shown in temporal lobe epilepsy and mesial temporal lobe sclerosis. 136 Collapsin response-mediated protein-2, and proteins involved in axonal outgrowth, path finding, and maintaining neuronal polarity have been demonstrated to be down-regulated in hippocampal tissue of patients with mesial temporal lobe epilepsy. 137 All of these have also been associated with other neurodegenerative disorders, such as Alzheimer's disease.…”
Section: Post-traumatic Epilepsymentioning
confidence: 99%
“…Chang and colleagues (2005) recently discovered a concerted effect of METH abuse and HIV on the amount of brain metabolites and cellular byproducts, specifically the neuronal marker NAA. NAA is a reliable neuronal marker as it has been shown to be detectable almost exclusively in neurons (Moffet et al, 1991;Simmons et al, 1991), and reductions in NAA often correlate with neuronal loss (for review, see Schuff et al, 2006). Chang et al (2005) found the lowest amount of NAA in frontal gray matter (-5.7%), frontal white matter (-6.1%), and the basal ganglia (-9%) relative to HIV seropositive non-drug abusers and HIV seronegative METH abusers.…”
Section: Hiv + Cocaine And/or Methamphetamine Neurotoxicitymentioning
confidence: 99%